Characteristics and outcome of critically ill patients with coronavirus disease-2019 (COVID-19) pneumonia admitted to a tertiary care center in the United Arab Emirates during the first wave of the SARS-CoV-2 pandemic. A retrospective analysis. - Khaled Ismail (Public Library of Science (PLoS), 2021)
Background The aim of this study was to describe the clinical characteristics and outcome of patients with coronavirus disease-2019 (COVID-19) pneumonia admitted to an intensive care unit (ICU) of a tertiary care center in the United Arab Emirates (UAE) and to identify early risk factors for in-hospital mortality in these patients. Methods A total of 371 adult patients (>18 years) admitted to the ICU of Al Ain Hospital between March 16 and July 19, 2020 with SARS-CoV-2 infection confirmed using real-time reverse transcription polymerase chain reaction (rt-PCR) on nasopharyngeal swabs were included. Results The mean patient age was 53 years (standard deviation = 13). Patients were mostly male (n = 314 [84.6%]) and of South Asian origin (n = 231 [62.3%]). Invasive mechanical ventilation was required in 182 (49.1%) patients for a median of 11 days (25-75% interquartile range: 6-17). During the ICU stay, renal replacement therapy was required in 87 (23.5%) and vasopressor therapy in 190 (51.2%) patients. ICU and hospital lengths of stay were 9 (IQ: 5-17) and 18 (IQ: 13-29) days, respectively and ICU and hospital mortality rates were both 20.2%. In a multivariable analysis with in-hospital mortality as the dependent variable, greater Acute Physiology and Chronic Health Evaluation II score on ICU admission, diarrhea prior to hospital admission, greater, admission from hospital ward, and higher lactate dehydrogenase levels and neutrophil:lymphocyte ratio on admission to the ICU were independently associated with higher risk of in-hospital mortality. Conclusion In this cohort of patients admitted to the ICU of a tertiary hospital in the UAE, COVID-19 pneumonia was associated with high morbidity and mortality rates. Identifying patients at high risk of death may help detect future therapeutic targets.